Factors influencing initiation of antenatal care in Ibadan, Nigeria (2011)
Objective: Late antenatal care (ANC) registration and irregular attendance have been implicated as factors preventing women from receiving the full benefits of effective ANC. Therefore, this study seeks to elicit the factors that impact pregnant women's timing of registration for ANC in a mission hospital, in Ibadan, Nigeria. Method: A cross-sectional study of 160 women attending the booking clinic over a 4-week period. A structured questionnaire was utilized to collect data on sociodemographic characteristics, index pregnancy, previous pregnancy and past obstetrical history. Result: Only 14 women (9.4%) booked at first trimester while 93 (62.4%) and 42 (28.2%) booked at second and third trimesters respectively. For previous and current pregnancies, the husband's instruction was the leading influence for booking, at 71 (45.8%) and 89 (57.4%) respectively. Knowledge of ANC timing, experience of loss of child and miscarriage were significant predictors of gestational age at booking. Conclusion: This study suggests the need for education at a pre-conceptual stage of the benefits of early initiation of ANC for women